On the decay of strength in Guilin red clay with cracks (Fracture and Structural Integrity, 2015)
In order to research the effect of cracks in red clay on shear strength through dry-wet cycle test, the experimenters used imaging software and a mathematical model to determine fractal dimension and crack ratio of surface cracks in red clay in Guilin, China. After each dry-wet cycle, direct shear tests were carried out on the sample, and such variables as matrix suction on the crack propagation process of red clay were analyzed. The mechanics model was established and obtained the critical condition of soil cracks. The results show that with the increase in the number of dry-wet cycles the shear strength of the samples would decrease. But the rule of shear strength of sample 3 is slightly different from samples 1 and 2. The shear strength of red clay has a good correlation with fractal dimension and crack ratio, which could be an identification index of the strength of red clay.
Keywords: Fractal dimension